Towards Elimination of Dog Mediated Human Rabies - Salome Durr (Frontiers Research Topics, 2017)
Rabies is an ancient zoonotic viral disease that still exerts a high impact on human and animal health. The disease is almost 100% fatal after clinical signs appear, and it kills tens of thousands of people per year worldwide, particularly in Africa and many parts of Asia. Although the disease in humans can be prevented by timely post-exposure prophylaxis, its access and affordability is limited in rabies endemic countries. With 99% of infections in humans caused by rabid domestic dog bites, controlling the infection in this reservoir population has been proven to be most effective to reduce and eliminate human rabies cases. In this context, this Research Topic invited contributions on the control and elimination of dog mediated human rabies. Publications on epidemiological, educational, policy-related and economic aspects of dog and human rabies surveillance, implementation of control in dogs and humans and scientific documentation of success stories were consolidated. We hope that these articles contribute to reaching the ambitious goal, set by key players in global health, of the elimination of dog mediated human rabies by 2030.